Valoración seminal en ovinos de raza corriedale y mestizos en la parroquia Cochapamba del cantón Saquisilí - Tapia Jácome, Lourdes Elizabeth (2014)
This researching evaluates the seminal quality of Corriedale sheep race and mestizos in the Parish Cochapamba Saquisilí Canton province of Cotopaxi, in order to determine the quality of semen to improve reproduction so to increase herd sheep. Because a single sheep male mates with many females, their semen quality depends that females have been prenen and therefore optimal breeding herd. This particular detail makes it a necessity to assess semen quality where not only analyzed , sperm concentration , motility , semen volume , appearance, color, Ph, but also serves to evaluate and establish the percentage sperm of living and dead, by staining techniques also called spermmorphology. The assessment of semen quality , is one of the most commonly used analysis tools ranking male sheep for direct mounting or service artificial insemination programs , through which a review of the potential fertility of sheep that is formed times. The work to be performed evaluates the macro and microscopic characteristics of Corriedale sheep and mestizos in the parish Cochapamba to rule out one of the problems that may be affecting fertility players.